BokoHaram Terrorism and The Futurology of Nigeria’s Development - AKINRINDE, Olawale Olufemi; Tegbe, Seun (Annals of Spiru Haret University. Economic Series, 2020)
This study interrogates the continued manifestation of the BokoHaram terrorism that inheres in the prevailing human securities challenges in Nigeria, and why the Nigerian developmental quests had failed and are bound to fail in the future should the human insecurity challenges that accounted for the BokoHaram terrorism are left unabated in Nigeria. Collected qualitative and archival data lend credence to the centrality of the proposition of this study that Boko-Haram terrorism would remain as long as the human security challenges such as poverty, inequalities, social injustice, unemployment, illiteracy remain unaddressed. This study therefore recommends a human-based approach to addressing the BokoHaram terrorism.